2013
DOI: 10.1371/journal.pone.0061332
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Biotrophic Lifestyle and Biocontrol Potential of Dark Septate Endophyte Harpophora oryzae to Rice Blast Disease

Abstract: The mutualism pattern of the dark septate endophyte (DSE) Harpophora oryzae in rice roots and its biocontrol potential in rice blast disease caused by Magnaporthe oryzae were investigated. Fluorescent protein-expressing H. oryzae was used to monitor the colonization pattern. Hyphae invaded from the epidermis to the inner cortex, but not into the root stele. Fungal colonization increased with root tissue maturation, showing no colonization in the meristematic zone, slight colonization in the elongation zone, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 63 publications
(68 reference statements)
5
90
0
Order By: Relevance
“…To obtain detailed information about the root colonization strategy employed by H. oryzae and its differences from that of M. oryzae and thus to choose the most appropriate time points for RNA isolation, we first inoculated roots of in vitro-cultivated rice plants with conidia of DsRed2-tagged H. oryzae strain Ho19red and eGFP-tagged M. oryzae strain Ho31gfp9, and documented infection using fluorescence and confocal microscopy (Supplementary Fig. S6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain detailed information about the root colonization strategy employed by H. oryzae and its differences from that of M. oryzae and thus to choose the most appropriate time points for RNA isolation, we first inoculated roots of in vitro-cultivated rice plants with conidia of DsRed2-tagged H. oryzae strain Ho19red and eGFP-tagged M. oryzae strain Ho31gfp9, and documented infection using fluorescence and confocal microscopy (Supplementary Fig. S6).…”
Section: Resultsmentioning
confidence: 99%
“…The DsRed2-tagged H. oryzae and eGFP-tagged M. oryzae 9 were used to monitor the infection process. The rice cultivar CO-39 ( Oryzae sativa ), for which the genome sequence is available44, was used as a compatible host plant for inoculation experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge on rice ecosystems, including the characterization and management of above and belowground microbial communities is of great relevance towards achieving this goal (Lenné and Wood 2011). Rice endophytic fungi may benefit their host by protecting them from biotic and abiotic stresses as well as promoting their growth (Le et al 2009;Redman et al 2011;Su et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For inoculated roots the best results were obtained at the CTT/AAGn locus where single inoculations and double inoculations generated clear bands. This revealed that both strains are able to simultaneously enter root tissue of a single plant and suggests that neither interdependent inhibition among the two fungi [60] nor effective defense reactions, enhanced local resistance possibly mediated by H2O2, nor reactive oxygen species occur from the host plant [61]. Up-to-date studies on co-colonization of plant roots are restricted to reports about dual colonization by different fungal species or by fungal and bacterial species, e.g., dark septate endophyte (DSE) fungi and ectomycorrhizal fungi in trees [62], DSE fungi and arbuscular mycorrhizal (AM) fungi in Medicago sativa L. [63], Piriformospora indica and Trichoderma harzianum in Piper nigrum L. [64], AM and DSE fungi in grasses [65] and the fungus Acremonium strictum Gams and bacterium Acinetobacter sp.…”
Section: Parallel In-root Detection Of Endophytic T Virens Strainsmentioning
confidence: 99%